Novas abordagens na caracterização de petróleos por espectrometria de massas FT-MS - Costa, Denys Ribeiro de Oliveira (2019)
The performance of the Orbitrap MS ultra-high-resolution mass analyzer was evaluated in the Brazilian petroleum study. The characteristics evaluated were: power of resolution and mass accuracy, during the characterization of samples of low TAN - (Total Acid Number), in six samples of oils. In addition, the objective was the detection of phenolic compounds in oils, class O, associated to the stabilization of emulsions. The phenolic compounds were studied, characterized by distribution in percentage of classes, DBE vs relative intensity, DBE vs carbon number and total carbon vs relative intensity. The study was performed by coupling the Electrospray ionization source, negative analysis mode, ESI(-), with the mass analyzer Orbitrap MS. The studied oils were divided into two groups, group 1 being emulsions and group 2 being non-emulsifying. The mass spectra of the oils and the respective fractions varied the ratio m/z ~ 200-1200 Da. The major classes found in the oil samples were: N, NO, NO2, NO3, O and O2. The predominant species in the six oils were (DBE 4) corresponding to monoaromatic phenols, aromatic compounds condensed with a ring (DBE 5), and two naphthenic rings (DBE 6). Di-, tri- and tetra-aromatic phenolic molecules (DBE 7, 10 and 13, respectively) were also detected. Finally, through SPE fractionation, it was possible to ionize and detect phenolic molecules with high ~C80 carbon numbers. Therefore, with the identification of these compounds of high molecular weight that have long carbon chains, which act as interfacial agents and align with the paraffins present in the oils, this phenomenon, justifies the formation of stable emulsions.